2019
DOI: 10.1088/1361-6552/ab3f18
|View full text |Cite
|
Sign up to set email alerts
|

Students making sense of motion in a vertical roller coaster loop

Abstract: Describing the motion in a vertical roller coaster loop requires a good understanding of Newton’s laws, vectors and energy transformation. This paper describes how first-year students try to make sense of force and acceleration in this example of non-uniform circular motion, which was part of a written exam. In addition to an analysis of the exam solutions by about 60 students, a group interview was performed a couple of weeks later with four students, who had all passed the exam. The interview allowed the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Newton's second law is present in the student discussions only as a very general principle. In the group discussion presented in [19], the students seemed surprised to discover that the geometrical vector sum of forces, e.g. at the turning point of a pendulum, gave directly the vector ma.…”
Section: Affordances Of Free-body Diagramsmentioning
confidence: 99%
“…Newton's second law is present in the student discussions only as a very general principle. In the group discussion presented in [19], the students seemed surprised to discover that the geometrical vector sum of forces, e.g. at the turning point of a pendulum, gave directly the vector ma.…”
Section: Affordances Of Free-body Diagramsmentioning
confidence: 99%
“…2. Jerk in amusement rides [1][2][3][4][5][6][7]14]; 3. Jerk in cosmology and space technology [91][92][93][94]; 4.…”
Section: Categorisation Of Jerk Applicationsmentioning
confidence: 99%
“…(2019) [6] Physics Education Q3 Assessed the first-year university understanding of the vertical motion on a roller coaster loop. It was found that students have partial conceptions about force and motion and contradictions in their responses and do not have a good understanding of abrupt changes in jerk.…”
Section: Source Sjr Purpose and Findings Commentsmentioning
confidence: 99%
See 2 more Smart Citations